Conducta Obstétrica ante Anomalía de Inserción Placentaria en Secundigesta de 39 años con periodo Intergenesico largo. - Verdezoto Sánchez, Ana Estefany (2021)
We must bear in mind that placental insertion anomalies are caused by an inadequate insertion or invasion of the placenta. In the placenta previa there is a development of the placenta in the lower uterine segment, located near or covering the internal cervical os. The placenta previa indices are increasing, which is why the timely identification of the factors from their prenatal controls is relevant, considering among the main ones maternal age, intergenetic period greater than 7 years and unscheduled pregnancy observed in the patient. For this reason, it was decided to study and follow-up from the first level of care to a second level to a 39-year-old second-pregnant patient with Partial Previa Occlusive Placenta with a long intergenic period, allowing to evaluate the management and conduct of Health professionals through controls prenatal care, ultrasound, laboratory tests, monitoring and surveillance of the maternal-fetal pairing. However, in the diagnosis and therapeutic evaluation of the end of pregnancy in order to prevent complications that put the life of the mother and child at risk.